Blood pressure fragmentation as a new measure of blood pressure variability: association with predictors of cardiac surgery outcomes - Costa, Madalena D.; Rangasamy, Valluvan; Behera, Alkananda; Mathur, Priyam; Khera, Tanvi; Goldberger, Ary L.; Subramaniam, Balachundhar (Frontiers in Physiology, 2024)
Author Contributions: MDC, ALG and BS conceived and designed the project. MDC and ALG developed the fragmentation analysis method. VR, AB, PM, TK, and BS collected and collated the patient data. MDC computed the fragmentation metric and performed the statistical data. MDC had full access to all of the data and takes responsibility for the integrity of the data and the accuracy of the data analysis. MDC and ALG drafted the manuscript and prepared the figures. All authors contributed to the discussion of the results, edited the manuscript and approved its final version.